Dynamics of a Stochastic Delayed Competitive Model with Impulsive Toxicant Input in Polluted Environments. (25th May 2014) - Deng, Meiling; Liu, Meng; Bai, Chuanzhi
Abstract : In the world today, with the rapid development of modern agriculture and industry, a large quantity of pollutants enter into ecosystems one by one, which is a threat to the persistence of the exposed populations. This paper investigates a stochastic delayed competitive system with impulsive toxicant input in a polluted environment. Under a simple condition, sufficient and necessary conditions for stability in the mean and extinction of each species are established. Some recent works are improved and extended greatly. Some numerical simulations are also included to illustrate and support the findings.